1994
DOI: 10.1007/bf01784335
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid negatively regulates β4 integrin expression and suppresses the malignant phenotype in a Lewis lung carcinoma cell line

Abstract: Retinoic acid (RA) is a potent inhibitor of the malignant phenotype and of tumour cell growth. We observed that in vitro RA treatment of a highly metastatic lung carcinoma cell line (C87) induced a marked reduction in the amount of the beta 4 integrin subunit. The downregulation of this adhesion molecule was assessed by immunofluorescence, immunoprecipitation, and northern analysis. In order to investigate the effects of RA on the malignant phenotype in C87 cells we performed morphological and functional analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
2

Year Published

1995
1995
2003
2003

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
3
6
2
Order By: Relevance
“…If GRASP, or a GRASP-like protein, acting through its alanine/proline-rich region and/or PDZ domain, associates with integrin receptors and/or associated proteins, it is conceivable that recruitment of cytohesin family members to this locus may similarly enhance the avidity of LFA-1 for ICAM-1. Such speculation would be consistent with previous studies demonstrating that treatment of various cell types with RA results in modulation of integrin adhesion (81)(82)(83)(84)(85)(86). For example, Katagiri and co-workers (87) have shown that retinoic acid potentiates cellular adhesion and aggregation mediated by LFA-1 and ICAM-1 in HL-60 cells undergoing neutrophilic differentiation.…”
Section: Bfa-insensitive Arf Gefs Are Differentially Expressed In P19supporting
confidence: 78%
“…If GRASP, or a GRASP-like protein, acting through its alanine/proline-rich region and/or PDZ domain, associates with integrin receptors and/or associated proteins, it is conceivable that recruitment of cytohesin family members to this locus may similarly enhance the avidity of LFA-1 for ICAM-1. Such speculation would be consistent with previous studies demonstrating that treatment of various cell types with RA results in modulation of integrin adhesion (81)(82)(83)(84)(85)(86). For example, Katagiri and co-workers (87) have shown that retinoic acid potentiates cellular adhesion and aggregation mediated by LFA-1 and ICAM-1 in HL-60 cells undergoing neutrophilic differentiation.…”
Section: Bfa-insensitive Arf Gefs Are Differentially Expressed In P19supporting
confidence: 78%
“…AI-trans-rinoic acid activates E-cadherin function SJ Vermeulen et al cribed for the decrease in B 16 melanoma cell aggregation (Edward et al, 1992) and for down-regulation of P4 integrins in LL4 cells (Gaetano et al, 1994). This need may be ascribed to the presence of serum in the culture medium and of albumin in the salt solution used for the aggregation assay (see Materials and methods).…”
Section: Discussionmentioning
confidence: 99%
“…In F9 mouse teratocarcinoma cells, laminin and fibronectin expression was upregulated upon RA exposure (Hierck et al, 1993;Huang and Chakrabarty, 1994;Ross et al, 1994). Integrin subunits (al, a5,a6, av, pl, 03) are usually upregulated except that p4 is downregulated in lung carcinomas (Dedhar et al, 1991;Defilippi et al, 1991;Gaetano et al, 1994;Ross et al, 1994). In vivo, both lack and excess of retinol and its active metabolites can cause congenital malformations, although the mechanisms might differ.…”
Section: Retinoic Acid and Developmentmentioning
confidence: 95%
“…Later, keratins, the intermediate filaments of epithelial cells, were shown to be upregulated by RA (Kim, 1992) as is the case for laminin, the major component of all basement membranes (Vasios et al, 1989;Vuolteenaho et al, 1990;Hierck et al, 1993;Huang and Chakrabarty, 1994;Ross et al, 1994). While in vitro data show that expression of some integrins is under RA control as well (Dedhar et al, 1991;Defilippi et al, 1991;Gaetano et al, 1994;Ross et al, 19941, and a6p4 is a major component of hemidesmosomes, linked to the intermediate filament network, we decided to study the expression of the p4 integrin subunit during normal and FtA induced abnormal development, with special emphasis on the heart.…”
mentioning
confidence: 91%